Efektivitas Instagram Marketing menggunakan aplikasi PLN Mobile di PT PLN Unit Induk Distribusi Jawa Timur - Zahra, Rizka Fatiha; Wikartika, Ira (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
The use of social media, particularly Instagram, has become an effective digital communication strategy for delivering public service information to the community. PT PLN (Persero) Unit Induk Distribusi Jawa Timur utilizes Instagram as a digital education platform to enhance public awareness and usage of the PLN Mobile application. This topic was selected due to existing challenges in communicating technical information to the public, including limited information reach and low understanding of application features. The methods applied in this study include direct observation of Instagram content, analysis of social media insights, and interviews with representatives from the Communication and General Affairs Division. The findings indicate that visual and interactive content, especially educational videos and storytelling formats, significantly increase audience engagement and content reach. Furthermore, Instagram functions effectively as a two-way communication medium that supports public understanding of digital services. These results highlight the importance of implementing adaptive, relevant, and easily understood digital educational content strategies to support the optimization of PLN Mobile utilization among the public.